2009
DOI: 10.4103/0970-0218.55283
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common ocular morbidities in adult population of Aligarh

Abstract: Aims and Objectives:To determine the prevalence of common ocular morbidities (cataract, refractive errors, glaucoma, and corneal opacities) and their demographic and sociocultural correlates.Settings and Design:The present cross-sectional study was conducted in the field practice areas of the Department of Community Medicine, JNMC, AMU, Aligarh, for a period of one year, from September 2005 to August 2006.Materials and Methods:Systematic random sampling was done to select the required sample size. All adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
45
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 15 publications
11
45
10
Order By: Relevance
“…In the present study prevalence of glaucoma irrespective of its type was found to be 3.4%, similar to the results obtained in the studies done by Garg P et al 14 and Martinez GS et al 20 but is higher than the prevalence found by Agrawal D et al, 7 Normalina M et al, 12 Khadse A et al 13 and Inaamul Haq et al 15 The prevalence of glaucoma was also found to be higher in the studies done by Ukponmwan CU 10 and Singh A et al…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the present study prevalence of glaucoma irrespective of its type was found to be 3.4%, similar to the results obtained in the studies done by Garg P et al 14 and Martinez GS et al 20 but is higher than the prevalence found by Agrawal D et al, 7 Normalina M et al, 12 Khadse A et al 13 and Inaamul Haq et al 15 The prevalence of glaucoma was also found to be higher in the studies done by Ukponmwan CU 10 and Singh A et al…”
Section: Discussionsupporting
confidence: 76%
“…Its prevalence rate was 37.4%. It is higher than the studies carried out in an urban population by Agrawal D et al, 7 Shrote VK et al, 8 Rizyal A et al, 9 Ukponmwan CU, 10 Khadse A et al, 13 Inaamul Haq et al, 15 Singh JP et al, 16 In the Aravind Comprehensive Eye Survey, 17 the prevalence of cataract in those aged 50 years and above was found to be 47.5%. The results in the Blue mountain eye study 18 conducted in nursing home residents also shows a higher prevalence of cataract.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…3 Study by Haq et al reported that refractive error was present in 25%. 4 Study by Singh et al in rural setting reported that prevalence of refractive error to be 40.8%. 5 Second most common cause of ocular morbidity was cataract (20.02%), the prevalence of cataract is significantly lesser in <35 years of age, as it is an age related disease.…”
Section: Discussionmentioning
confidence: 99%
“…2 Haq et al also reported that cataract prevalence was 21.7% in their study. 4 Study by Singh et al stated that cataract prevalence was 40.4%. 5 In present study allergic conjunctivitis was third commonest cause of ocular morbidity in our district.…”
Section: Discussionmentioning
confidence: 99%